Molybdenum Disulfide Nanosheets Aligned Vertically on Carbonized Silk Fabric as Smart Textile for Wearable Pressure-Sensing and Energy Devices - Lu, Wangdong; Yu, Peng; Jian, Muqiang; Wang, Haomin; Wang, Huimin; Liang, Xiaoping; Zhang, Yingying (ACS applied materials & interfaces, 2020)
Flexible electronics have gained considerable research concern due to their wide prospect for health monitoring, soft robotics, and artificial intelligence, wherein flexible pressure sensors are necessary components of wearable devices. It is well known that the synergistic functions and multiscale structures of hybrid materials exert tremendous effects on the performance of flexible devices. Herein, inspired by the unique structure of the faceplate of sunflowers, we construct a hierarchical structure by in situ grown vertically aligned molybdenum disulfide (MoS2) nanosheets on carbonized silk fabric (MoS2/CSilk), which is applied as the sensing material in flexible pressure sensors. The MoS2/CSilk sensor displayed high sensitivity and good stability. We demonstrated its applications in monitoring subtle physiology signals, such as pulse wave and voice vibrations. In addition, it served as electrodes in lithium-ion batteries. The MoS2/CSilk electrode delivered ultrahigh first-cycle discharge and charge capacities of 2895 and 1594 mA h g–1, respectively. The MoS2/CSilk electrode exhibited a high capacity of 810 mA h g–1 with a CE close to 100% even after 300 cycles, suggesting good stability. The excellent overall performances are ascribed to the unique structure of the MoS2/CSilk and the synergistic effect of CSilk and MoS2. The concept and strategy of this work can be extended to the design and fabrication of other multifunctional devices.